Nilai-Nilai Pendidikan Dalam Shalat Jenazah - Raju Pratama Marronis; Fajri Massaid; Zaky Raihan Febrianto; Windi Alya Ramadhani; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2023)
. It is an obligation for every Muslim to organize his brother's body if he dies. One of the obligations This is praying for the corpse. There are various kinds of attitudes and the practice of Muslims in praying for corpses as in determine who the person has the right to be the imam in prayer corpses, and whether or not it is permissible to pray over the bodies of those who commit immoral acts such as the bodies of adulterers and the bodies of corruptors who have given birth polemics and debates among scientific experts today. Various The various attitudes of the Muslims mentioned above are also based on the hadiths of the Prophet Muhammad, the qualities of which are authentic, hasan and dhaif. Therefore, this research will discuss how proof is and an understanding of the hadith regarding funeral prayers which is more focused on hadiths about who is the person who has the right to lead the funeral prayer and hadith about the Apostle not praying for the bodies of those who commit immoral acts, such as bodies of adulterers and bodies of corruptors.